2007
DOI: 10.1007/s00128-007-9282-8
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of The Acute Toxicity of Cypermethrin and λ-Cyhalothrin to Channa Punctatus

Abstract: In the present study, the acute toxicity of the pyrethroid pesticides, cypermethrin and lambda-cyhalothrin was conducted for a 96 h period using Channa punctatus. The LC(50) values of cypermethrin and lambda-cyhalothrin were found to be 0.4 mg/L and 7.92 mug/L, respectively. The lambda-cyhalothrin was found to be about 50 times more toxic to the fish than cypermethrin. The behavioral pattern of C. punctatus got severely altered in each group due to pesticide treatment. The results suggested that even at low co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 13 publications
5
30
3
Order By: Relevance
“…Kumar et al (2007) tested concentrations of 0.3, 0.4, 0.5 and 0.6mg/L of Cypermethrin in Channa punctatus, which presented the first clinical signs after three hours of exposure, incompatible with this study, which observed that the aforementioned clinic signs have started before completing an hour of exposure. Galeb (2010) when exposing Silver catfish under Deltamethrin effects, observed that the body color of the animals changed, showing a whitish color; this result was also observed in this study, being more perceptible in post-mortem alterations; they also presented hemorrhagic dots and ulcerated lesions throughout their bodies.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Kumar et al (2007) tested concentrations of 0.3, 0.4, 0.5 and 0.6mg/L of Cypermethrin in Channa punctatus, which presented the first clinical signs after three hours of exposure, incompatible with this study, which observed that the aforementioned clinic signs have started before completing an hour of exposure. Galeb (2010) when exposing Silver catfish under Deltamethrin effects, observed that the body color of the animals changed, showing a whitish color; this result was also observed in this study, being more perceptible in post-mortem alterations; they also presented hemorrhagic dots and ulcerated lesions throughout their bodies.…”
Section: Discussioncontrasting
confidence: 97%
“…Such results corroborate with Polat et al (2002), who tested Cypermethrin in guppies (Poecilia reticulata) and Borges (2007), who tested Cypermethrin in Silver catfish (Rhamdia quelen). Kumar et al (2007), when exposing Channa punctatus to Cypermethrin, also reported such alterations.…”
Section: Discussionmentioning
confidence: 79%
“…The most important behavioral changes observed in this paper were related to breathing and neurological disorders; such alterations have corroborated conclusions of authors Polat et al (2002), Yilmaz et al (2004), regarding their testing of Cypermethrin in Guppies (Poecilia reticulata); Borges (2005) and Borges (2007) regarding their testing of Cypermethrin in Silver Catϐish (Brazilian "Jundiá", Rhamdia quelen) and Kumar et al (2007) who exposed Channa punctatus to Cypermethrin on their studies. The aforementioned authors have also related such alterations.…”
Section: Behavioral Changes and Mortalitysupporting
confidence: 89%
“…But information on the toxicity of these pesticides to non-target aquatic organisms is scarce. Cypermethrin has already been reported as highly toxic to fish (Kumar et al 2007;Saha and Kaviraj 2008). Sporadically, it has also been reported that the toxicity of cypermethrin to fish varies with stereochemical structure (Polat et al 2002), mixtures of their isomers (Yilmaz et al 2004) and formulation.…”
Section: Introductionmentioning
confidence: 99%